Can Mentoring Alleviate Family Disadvantage in Adolescence? A Field Experiment to Improve Labor-Market Prospects - Sven Resnjanskij; Jens Ruhose; Simon Wiederhold; Ludger Woessmann (Institute of Labor Economics (IZA), 2021)
We study a mentoring program that aims to improve the labor-market prospects of school- attending adolescents from disadvantaged families by offering them a university-student mentor. Our RCT investigates program effectiveness on three outcome dimensions that are highly predictive of adolescents' later labor-market success: math grades, patience/social skills, and labor-market orientation. For low-SES adolescents, the one-to-one mentoring increases a combined index of the outcomes by half a standard deviation after one year, with significant increases in each dimension. Part of the treatment effect is mediated by establishing mentors as attachment figures who provide guidance for the future. The mentoring is not effective for higher-SES adolescents. The results show that substituting lacking family support by other adults can help disadvantaged children at adolescent age.
Keywords: I24; J24; H52; 330; mentoring; disadvantaged youths; adolescence; school performance; patience; social skills; labor-market orientation; field experiment